EFEKTIVITAS KERJA PEGAWAI LEMBAGA PEMASYARAKATAN KELAS II A MANADO - KRTISTIAN GANI MANESSU; VERY LONDA; FEMMY TULUSAN (JURNAL ADMINISTRASI PUBLIK, 2022)
Institution Employees. This study used descriptive qualitative research methods. The data collection technique used is the result of observation, interviews and documentation. In this study, the data analysis techniques used were data reduction, data display, and verification and conclusion drawing. The results showed that employees at the Class II A Manado Correctional Institution had the ability to adjust themselves through work mapping, work time division, use of work facilities, all planned tasks were carried out properly and all planned tasks were carried out. well. So it can be concluded that the ability to adapt through work mapping, work time sharing, use of work facilities and the achievement of work results in accordance with the plan, is well received by the leadership and in solving prisoner problems and the satisfaction felt by employees can be seen from the awards received. in the form of performance allowances, training and career paths as well as cooperation and mutual respect between the leadership and staff..Keywords : Work Effectiveness, Correctional Institution